Degradation and residues of trifluralin and metalaxy in soils treated with 14C-trifluralin and 14C-metalaxyl, under laboratory conditions - Musumeci, Maria Raphaela; Ruegg, Elza F. (Pesquisa Agropecuaria Brasileira, 2014)
The behaviour of the herbicide 14C-trifluralin and the fungicide 14C-metalaxyl was studied under laboratory conditions in Red Latosol and Yellow Red Podzol soils in samples kept flooded, sterilized and with humidity equivalent to 60% of the water field capacity. After 240 days in the soil samples treated with 14C-trifluralin bound residue was 6% in Red Latosol and 17% in the Podzol soil. Trifluralin degradation was higher in the Podzol soil with four metabolites detected in the flooded soil samples. Trifluralin metabolism was increased in nonsterile soil samples. Trifluralin volatilization was detected since 24 hours after addition to soils and it was constant until 12 to 33%, with less volatily from soils kept flooded.14C-metalaxyl degradation was higher in Red Latosol soil, but flooded conditions enchanced metalaxyl metabolism in both soil types with the detection of two metabolites. Metabolism was duo to microbial degradation since almost no degradation occurred in sterilized soil samples. Bound residue was 15% in Red Latosol, and 25% in the Podzol soil.